Influence of teachers' professionalism, class size and instructional materials on lower primary school pupils' performance in social studies in Osun State Nigeria - Babatunde Adeniyi ADEYEMI; Grace Olajumoke JUBRIL (African Journal of Behavioural and Scale Development Research, 2019)
The study determined the lower primary school pupils' performance in Social Studies. It also examined the relative influence of each teachers' professionalism, class size and instructional materials on lower primary school pupils' performance in Social Studies and finally examined the combined influence of teachers' professionalism, class size and instructional materials on lower primary school pupils' performance in Social Studies. These were with the view to providing information on how the influence of each of teachers' professionalism, class size and instructional materials could bring about improved performance in Social Studies among lower primary school pupils in Osun State. The study employed descriptive survey design and the target population comprised the public lower primary school pupils and their teachers in Ife East Local Government area of Osun State. The sample size comprised 400 pupils and 40 Social Studies teachers. Ten lower primary schools were selected in the local government area using simple random technique. From each of the schools, forty (40) pupils from primary three were selected, using simple random sampling technique while four teachers were purposively selected from each school based on the fact that they were Social Studies teachers. Three instruments were used for the study. One research question was raised and answered and two hypotheses were tested and verified. Data collected were analyzed using Frequency Counts, Percentages, Bar Charts and Multiple Regression. The results showed that lower primary school pupils demonstrated moderate performance (57%) in Social Studies. The results also showed that teachers' professionalism (t=2.653, β=.349, p=.012) class size (t= 2.439, β=.271, p=0.020) and instructional materials (t= -3.912, β=-.419, p=.000) had significant influence on pupils' performance in Social Studies. Finally, there was significant influence of teachers' professionalism, class size and instructional materials on lower primary school pupils' performance in Social Studies (t= 33.391, P<0.05). The study concluded that teachers' professionalism, class size and instructional materials are capable of enhancing academic performance in Social Studies among lower primary school pupils in Osun State.